Corona-resistant insulating paint for enameled wire and preparation method of corona-resistant insulating paint

By using hybrid polyimide, composite nanoparticles and composite solvents in the corona-resistant insulating paint for enameled wires, a polyimide backbone and crosslinking network that is both rigid and flexible is solved, and the problem of insufficient corona and flame retardant performance of existing paints is achieved, and higher insulation, solvent resistance and flame retardant performance are achieved.

CN119875497AActive Publication Date: 2025-04-25TONGLING JINGLONG ELECTRIC MATERIAL

Patent Information

Application Number
CN202510358823.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The corona resistance and flame retardant properties of existing corona-resistant enameled wire paint need to be further improved.

Method used

Using a combination of hybrid polyimide, composite nanoparticles and composite solvents, a polyimide backbone with both rigidity and softness is constructed through a polysiloxane chain extender, and a synergistic crosslinking network is formed through nanotitanium dioxide particles and fluorine group-modified silicon aluminum-boron composite particles.

Benefits of technology

It significantly improves the corona, insulation, solvent resistance and flame retardant properties of insulating paint, enhances the density and mechanical toughness of the coating, and improves the tolerance to ultraviolet rays and high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses corona-resistant insulating paint for enameled wires and a preparation method of the corona-resistant insulating paint, and belongs to the technical field of insulating paint preparation, and the corona-resistant insulating paint specifically comprises the following raw materials in parts by weight: 70-80 parts of hybrid polyimide, 10-15 parts of composite nanoparticles, 30-36 parts of a composite solvent and 6-8 parts of an auxiliary additive, a chain extender with a siloxane chain segment as a chain segment structure is prepared through telomerization, after chain extension is conducted on a polyamide acid chain segment containing a large number of fluorine groups and chain segment direct nanometer titanium dioxide particles, hot pressing amidation is conducted to obtain hybrid polyimide, silicon-aluminum-boron composite nanometer particles are prepared, the surface of each silicon-aluminum-boron composite nanometer particle is modified with a perfluoro group and double bonds, and the high-temperature-resistant performance of the silicon-aluminum-boron composite nanometer particles is achieved. Cross-linking the composite nanoparticles and the hybrid polyimide through free radical reaction, and mixing with auxiliary materials to finally prepare the corona-resistant insulating paint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating varnish preparation, and in particular to a corona-resistant insulating varnish for enameled wire and a preparation method thereof. Background Art

[0002] The development of corona-resistant insulating paint has gone through several stages from improving electrical insulation to enhancing corona resistance. Initially, the paint focused on improving electrical insulation. As the demand for high-voltage equipment increased, corona resistance gradually became a research focus. In the 1980s, materials such as polyurethane and epoxy resin enhanced the corona resistance of the paint film, and flame retardants were added to cope with high temperatures. In the 21st century, research on strengthening flame retardancy and using phosphorus and nitrogen flame retardants. At the same time, nanotechnology improved the electrical and thermal stability of the paint film. Today, modern paints not only have excellent corona resistance, but also have flame retardancy and high temperature resistance, thus meeting the needs of high-voltage electrical equipment.

[0003] For example, the prior art CN105219233B discloses a corona-resistant wire enameled paint and a preparation method thereof. Under the condition of stirring in a toothed disc disperser, an inorganic oxide raw material is added to an organic solvent, the linear speed of the toothed disc disperser is controlled to be 10-22 m / s, the shear dispersion time is 0.5-2h, and then grinding is performed in a grinder, the linear speed of the grinder is controlled to be 15-25 m / s, and the grinding time is 3-6h to prepare an inorganic oxide pre-dispersion liquid with D50<150nm and a solid content of 50-70%, a coupling agent is added to the inorganic oxide pre-dispersion liquid to form a corona-resistant modifier, and the corona-resistant modifier and the paint body are stirred at 70-100°C to prepare the corona-resistant wire enameled paint.

[0004] However, the above invention is to modify the metal oxide with a coupling agent to obtain a corona-resistant modifier, thereby obtaining a corona-resistant wire enamel. However, the metal oxide modified with the silane coupling agent only improves the compatibility with the paint body, but does not form a cross-linked structure with the organic chain segment of the paint body, resulting in the need to further improve the dispersibility of the corona-resistant modifier in the paint, causing the corona-resistant modifier to agglomerate in the paint, so that the corona resistance and wear resistance of the material need to be further improved. Summary of the invention

[0005] The object of the present invention is to provide a corona-resistant insulating varnish for enameled wire and a preparation method thereof, so as to solve the technical problem that the corona-resistant performance and flame-retardant performance of the insulating varnish in the prior art need to be further improved.

[0006] The object of the present invention can be achieved by the following technical scheme: A corona-resistant insulating varnish for enameled wire, comprising the following raw material components in parts by weight: 70-80 parts of hybrid polyimide, 10-15 parts of composite nanoparticles, 30-36 parts of composite solvent and 13-19 parts of auxiliary additives;

[0007] The preparation method of the hybrid polyimide comprises the following steps:

[0008] A1, adding hybrid polyamic acid and N, N-dimethylformamide into a reactor, stirring at room temperature for 10-15 minutes, adding modification liquid to the reactor, stirring for 3-5 minutes after the addition is complete, standing for 20-30 minutes, and post-treating to obtain composite polyamic acid;

[0009] A2. Thermal imidization of the composite polyamic acid to obtain a hybrid polyimide.

[0010] Furthermore, the composite solvent includes: butyl acetate, toluene and isopropyl alcohol; the auxiliary additives include: ultraviolet absorber, thickener, leveling agent, initiator and hardener;

[0011] Further, the usage ratio of butyl acetate, toluene and isopropyl alcohol is 180-200g:80-100g:40-60g; the usage ratio of ultraviolet absorber, thickener, leveling agent, initiator and hardener is 2-3g:3-5g:1-2g:2-3g:5-6g;

[0012] Furthermore, the ultraviolet absorber is one or both of 2-hydroxy-4-octyloxybenzophenone and bis(2,2,6,6-tetramethylpiperidinyl)sebacate; the thickener is one or more of sodium carboxymethyl cellulose, polyvinyl alcohol and sodium polyacrylate; the leveling agent is one or more of dimethyl silicone oil, ethoxylated silicone oil and polyether modified silicone oil; the initiator is one or both of potassium persulfate and azobisisobutyronitrile; the hardener is one or more of maleic anhydride, diaminodiphenylmethane and diaminodiphenyl ether.

[0013] The reaction equation for preparing hybrid polyimide is:

[0014]

[0015] The reaction principle for preparing hybrid polyimide is as follows: ethyl titanate is hydrolyzed in deionized water to produce a titanium hydroxide structure, and titanium hydroxide and hybrid polyamic acid form a hydrogen bond structure, so that iron hydroxide is evenly dispersed on the surface of the hybrid polyamic acid segment. Finally, as the thermal imidization proceeds, the iron hydroxide is continuously dehydrated to form a titanium dioxide structure, and finally a hybrid polyimide is prepared.

[0016] Further, in step A1, the amount ratio of hybrid polyamic acid, N,N-dimethylformamide and modification liquid is 8-10g:40-50mL:10mL, wherein the modification liquid is obtained by mixing and stirring ethyl titanate and deionized water at an amount ratio of 1-2g:10mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction kettle is lowered to room temperature, the reaction liquid is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 60-80°C, and the modified polyamic acid is obtained after reduced pressure distillation until no liquid is produced;

[0017] Furthermore, in step A2, the preparation method of the hybrid polyimide is as follows: the hybrid polyamic acid is transferred to an electric thermostat, after nitrogen protection is introduced, the electric thermostat is heated to 100°C, and after heat preservation for 60-80 minutes, the electric thermostat is further heated to 200°C, and after heat preservation for 1 hour, the electric thermostat is heated to 300°C again, and after heat preservation for 1 hour, it is naturally cooled to room temperature to obtain a hybrid polyimide.

[0018] Furthermore, the preparation method of the hybrid polyamic acid comprises the following steps:

[0019] B1. Add (E)-but-2-ene-1,4-diamine and N,N-dimethylformamide to a reactor at a temperature of 0-5°C, keep warm and stir until the reactants are completely dissolved, add 4,4'-(hexafluoroisopropylene) diphthalic anhydride to the reactor in three portions, and after the addition is completed, stably raise the temperature of the reactor to 30-50°C, keep warm and react for 2-4 hours, and post-treat to obtain modified polyamic acid;

[0020] B2. Add modified polyamic acid, modified chain extender, benzoic acid and N,N-dimethylformamide into a reactor and stir. Heat the reactor to 60-80°C, keep warm and stir for 60-80 minutes, and perform post-treatment to obtain hybrid polyamic acid.

[0021] Further, in step B1, the amount ratio of (E)-but-2-ene-1,4-diamine, N,N-dimethylformamide and 4,4'-(hexafluoroisopropylene) diphthalic anhydride is 2.0-2.4g:80-100mL:10.7-11.2g, and the post-treatment includes: after the reaction is completed, the temperature of the reaction kettle is lowered to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 60-80°C, and the reaction solution is distilled under reduced pressure until no liquid is produced to obtain a modified polyamic acid;

[0022] Furthermore, in step B2, the amount ratio of modified polyamic acid, modified chain extender, benzoic acid and N,N-dimethylformamide is 8-10g:2-3g:0.3-0.5g:40-50mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 60-80°C, and the hybrid polyamic acid is obtained after distillation under reduced pressure until no liquid is produced.

[0023] The reaction equation for preparing hybrid polyamic acid is:

[0024]

[0025] The reaction principle for preparing hybrid polyamic acid is as follows: the amino group on (E)-but-2-ene-1,4-diamine and the anhydride group on 4,4'-(hexafluoroisopropylene) diphthalic anhydride undergo a ring-opening reaction under heating conditions to ultimately prepare a modified polyamic acid with a long-chain structure. The long-chain structure forms an anhydride-terminated structure by controlling the amount ratio of the reactants, and reacts with the epoxy group on the surface of the modified chain extender to ultimately prepare a hybrid polyamic acid.

[0026] Furthermore, the preparation method of the modified chain extender comprises the following steps:

[0027] C1. Add 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3-dimethyl-1,1,3,3-tetravinyldisiloxane and diethyl ether into a reactor and stir. Add 98wt% concentrated sulfuric acid during stirring. After stirring at room temperature for 8-10h, add sodium bicarbonate powder into the reactor to adjust the pH value of the system to 8-9. Post-treat to obtain modified silicone oil.

[0028] C2. Add modified silicone oil, benzoic acid, aluminum chloride and dimethyl sulfoxide into a reactor and stir. The temperature of the reactor is lowered to 0-5°C. Saturated hydrogen peroxide solution is added dropwise to the reactor under stirring and heat preservation. The addition operation is maintained for 3-4 hours. After the addition is completed, the reactor is stirred and heat preservation for 1 hour. The modified chain extender is obtained by post-treatment.

[0029] Further, in step C1, the amount ratio of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3-dimethyl-1,1,3,3-tetravinyldisiloxane, ether and 98wt% concentrated sulfuric acid is 7-9g:2-3g:50-80mL:10-12mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction kettle is lowered to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 60-80°C, and the modified silicone oil is obtained after distillation under reduced pressure until no liquid is produced;

[0030] Furthermore, in step C2, the amount ratio of modified silicone oil, benzoic acid, aluminum chloride, dimethyl sulfoxide and saturated hydrogen peroxide solution is 12-16g:3-5g:0.5-0.8g:60-80mL:10-12mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 60-80°C, and the modified chain extender is obtained after distillation under reduced pressure until no liquid is produced.

[0031] The reaction equation for preparing the modified chain extender is:

[0032]

[0033] The reaction principle for preparing the modified chain extender is as follows: under the catalysis of concentrated sulfuric acid, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 1,3-dimethyl-1,1,3,3-tetravinyldisiloxane undergo a polymerization reaction to form a modified silicone oil with a large number of double bond structures, and the double bonds are further converted into epoxy groups through peracid oxidation to finally prepare the modified chain extender.

[0034] Furthermore, the preparation method of the composite nanoparticles comprises the following steps:

[0035] D1. Slowly add methyl orthosilicate, tributyl borate and deionized water to a three-necked flask equipped with a thermometer, a stirrer and a cooling reflux device in sequence. Heat the three-necked flask to reflux under stirring, keep it warm and stir for 4-5 hours, remove the cooling reflux device and replace it with a distillation device, then add aluminum isopropoxide to the reactor, heat the three-necked flask to 115-120° C., keep it warm for 10-20 minutes, and post-treat to obtain modified nanoparticles;

[0036] D2. Add modified nanoparticles, toluene, composite modifier and deionized water into the reactor, use protective sodium hydroxide solution to adjust the system pH to 8-10, then increase the temperature of the reactor to 30-40°C, keep warm and stir for 30-40 minutes, and post-treat to obtain composite nanoparticles.

[0037] The reaction principle for preparing composite nanoparticles is as follows: under reflux conditions, methyl orthosilicate and tributyl borate are hydrolyzed to produce a cross-linked structure, and under heating and distillation conditions, aluminum isopropoxide continues to hydrolyze to form a supplement to the structure, which is then calcined to prepare modified nanoparticles. Finally, after modification with a composite modifier, perfluorinated groups and double bond structures are introduced onto the surface of the modified nanoparticles to prepare composite nanoparticles.

[0038] Further, in step D1, the amount ratio of methyl orthosilicate, tributyl borate, deionized water and aluminum isopropoxide is 6-8g:2-3g:60-80mL:5-6g, and the post-treatment is as follows: the material is transferred to a tubular furnace, nitrogen is introduced for protection, the tubular heating furnace is increased to 500-600°C at a rate of 5-6°C / min, and the temperature is kept for 5-6h, and then naturally cooled to 200-300°C, the nitrogen is disconnected, and water vapor is introduced at a rate of 100-120sccm, and the temperature is kept for 2-3h, and then naturally cooled to obtain modified nanoparticles;

[0039] Furthermore, in step D2, the modified nanoparticles, anhydrous ethanol, composite modifier and deionized water are used in a ratio of 6-8 g: 20-25 mL: 10-15 mL: 10-15 mL, wherein the composite modifier is obtained by mixing perfluorooctyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and anhydrous ethanol in a ratio of 1-2 g: 1-2 g: 10-15 mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with anhydrous ethanol and deionized water, and the filter cake is transferred to a drying oven at a temperature of 60°C, and vacuum dried to constant weight to obtain composite nanoparticles.

[0040] The present invention also proposes a method for preparing a corona-resistant insulating paint for enameled wire: hybrid polyimide, composite nanoparticles and composite solvent are added to a reactor and stirred; after the temperature of the reactor is increased to 60-80°C, an initiator is added; after the reaction is kept warm and stirred for 40-60 minutes, an ultraviolet absorber, a thickener, a leveling agent and a hardener are added to the reactor; the reaction is kept warm and stirred for 10-15 minutes; and the reaction is naturally cooled to room temperature to obtain the corona-resistant insulating paint.

[0041] The reaction principle for preparing corona-resistant insulating paint is as follows: under heating and catalysis of initiator, the double bonds on the hybrid polyimide and the double bonds modified on the surface of the composite nanoparticles undergo free radical addition reaction to form a cross-linked structure, so that the composite nanoparticles are evenly dispersed inside the matrix, and auxiliary materials are added to finally prepare the corona-resistant insulating paint.

[0042] The present invention has the following beneficial effects:

[0043] 1. The present invention constructs a rigid and flexible polyimide main chain by introducing a polysiloxane chain extender. The flexible siloxane chain segment is combined with the rigid aromatic ring through hydrogen bonds, thereby improving the interface compatibility and mechanical toughness while maintaining the high temperature resistance of the material, and inhibiting local discharge caused by microcracks. Secondly, the nano-titanium dioxide particles and the silicon-aluminum-boron composite particles modified with fluorine groups work synergistically. Titanium dioxide disperses the electric field evenly through its high dielectric properties, and the fluorine groups capture free electrons and form a hydrophobic barrier by virtue of their strong electronegativity, blocking moisture penetration and active oxygen erosion. A three-dimensional cross-linked network is further constructed through free radical reactions, and the double bonds on the surface of the silicon-aluminum-boron particles form dynamic bonds with the polyimide main chain. Energy dissipation is achieved through molecular chain slippage under electric field stress, avoiding breakdown caused by charge concentration, thereby significantly improving the anti-corona, insulation and solvent resistance of the insulating paint.

[0044] 2. The siloxane chain extender prepared by the present invention forms a rigid-flexible structure through flexible chain segments and the rigid main chain of polyimide, which not only maintains the high-strength characteristics of the material, but also disperses mechanical stress through molecular chain slippage. Combined with the hard support and uniform dispersion of nano-titanium dioxide particles, physical cross-linking points are formed to resist friction and wear, and the surface crack propagation is inhibited. In the combustion process, the fluorine-containing free radicals generated by the high-temperature decomposition of fluorine groups interrupt the combustion chain reaction. When the silicon aluminum boron particles are heated, a dense oxide layer is formed on the surface to isolate oxygen and heat transfer. The boron element catalyzes the rapid generation of a carbonized layer, which further blocks the spread of flames. The fluorine-group-modified nanoparticles strongly combine with the polymer interface to inhibit crack propagation. The rigid support of the cross-linked network complements the flexible buffer of the siloxane chain, thereby significantly improving the flame retardancy and wear resistance of the insulating paint.

[0045] 3. A large number of fluorine groups in the insulating varnish prepared by the present invention absorb ultraviolet light energy through strong electronegativity and convert it into heat energy for release. Its chemical inertness forms a dense barrier to block the direct damage of ultraviolet rays to the polymer main chain. At the same time, the hydrophobic property inhibits the synergistic photooxidation reaction of water vapor. The nano-titanium dioxide particles reflect and scatter ultraviolet rays by virtue of their high refractive index characteristics, reducing their penetration depth. The evenly dispersed particles are chemically bonded to the polymer chains to synergistically inhibit the breakage of the molecular chains. The perfluorinated groups modified on the surface of the silicon-aluminum-boron composite nanoparticles are cross-linked through double bonds and polyimide chain segments through free radical reactions to form a spatial cross-linked network, which fixes the position of the particles to enhance the density of the coating and reduce the expansion of ultraviolet-induced microcracks. The high thermal conductivity assists the diffusion of heat energy to avoid local temperature rise and accelerated aging, thereby significantly improving the anti-ultraviolet performance of the insulating varnish. DETAILED DESCRIPTION

[0046] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Example 1

[0048] The present embodiment provides a method for preparing a modified chain extender for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0049] Step ①: Preparation of modified silicone oil

[0050] Weigh: 700.0g2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 200.0g1,3-dimethyl-1,1,3,3-tetravinyldisiloxane and 5000.0mL ether, add into the reactor and stir, add 1000.0mL98wt% concentrated sulfuric acid during stirring, stir at room temperature for 8h, add sodium bicarbonate powder into the reactor, adjust the pH of the system to 8, after the reaction is completed, wait for the temperature of the reactor to be lowered to room temperature, transfer the reaction solution into a rotary evaporator, raise the temperature of the rotary evaporator to 60°C, and distill under reduced pressure until no liquid is produced to obtain modified silicone oil.

[0051] Step ②: Preparation of modified chain extender

[0052] Weigh: 1200.0g modified silicone oil, 300.0g benzoic acid, 50.0g aluminum chloride and 6000.0mL dimethyl sulfoxide, add to the reactor and stir, the temperature of the reactor is reduced to 5°C, 1000.0mL saturated hydrogen peroxide solution is added dropwise to the reactor under stirring and insulation, the dropping operation is maintained for 3h, after the addition is completed, the mixture is stirred for 1h, after the reaction is completed, the temperature of the reactor is reduced to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 60°C, and the modified chain extender is obtained after distillation under reduced pressure until no liquid is produced.

[0053] Example 2

[0054] The present embodiment provides a method for preparing a modified chain extender for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0055] Step ①: Preparation of modified silicone oil

[0056] Weigh: 900.0g2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 300.0g1,3-dimethyl-1,1,3,3-tetravinyldisiloxane and 8000.0mL ether, add into the reactor and stir, add 1200.0mL98wt% concentrated sulfuric acid during stirring, stir at room temperature for 10h, add sodium bicarbonate powder into the reactor, adjust the system pH to 9, after the reaction is completed, wait for the temperature of the reactor to be lowered to room temperature, transfer the reaction solution into a rotary evaporator, raise the temperature of the rotary evaporator to 80°C, and distill under reduced pressure until no liquid is produced to obtain modified silicone oil.

[0057] Step ②: Preparation of modified chain extender

[0058] Weigh: 1600.0g modified silicone oil, 500.0g benzoic acid, 80.0g aluminum chloride and 8000.0mL dimethyl sulfoxide, add to the reactor and stir, the temperature of the reactor is reduced to 0°C, 1200.0mL saturated hydrogen peroxide solution is added dropwise to the reactor under stirring and insulation, the dropping operation is maintained for 4h, after the addition is completed, the mixture is stirred for 1h, after the reaction is completed, the temperature of the reactor is reduced to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 80°C, and the modified chain extender is obtained after distillation under reduced pressure until no liquid is produced.

[0059] Example 3

[0060] The present embodiment provides a method for preparing a modified chain extender for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0061] Step ①: Preparation of modified silicone oil

[0062] Weigh: 800.0g2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 240.0g1,3-dimethyl-1,1,3,3-tetravinyldisiloxane and 7200.0mL ether, add into the reactor and stir, add 1200.0mL98wt% concentrated sulfuric acid during stirring, stir at room temperature for 9h, add sodium bicarbonate powder into the reactor, adjust the system pH to 9, after the reaction is completed, wait for the temperature of the reactor to be lowered to room temperature, transfer the reaction solution into a rotary evaporator, raise the temperature of the rotary evaporator to 70°C, and distill under reduced pressure until no liquid is produced to obtain modified silicone oil.

[0063] Step ②: Preparation of modified chain extender

[0064] Weigh: 1500.0g modified silicone oil, 400.0g benzoic acid, 72.0g aluminum chloride and 7200.0mL dimethyl sulfoxide, add to the reactor and stir, the temperature of the reactor is reduced to 3°C, 1200.0mL saturated hydrogen peroxide solution is added dropwise to the reactor under stirring and insulation, the dropping operation is maintained for 4h, after the addition is completed, the mixture is stirred for 1h, after the reaction is completed, the temperature of the reactor is reduced to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 70°C, and the modified chain extender is obtained after distillation under reduced pressure until no liquid is produced.

[0065] Example 4

[0066] The present embodiment provides a method for preparing a hybrid polyamic acid for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0067] Step (i) Preparation of modified polyamic acid

[0068] Weigh: 200.0g (E)-but-2-ene-1,4-diamine and 8000.0mL N,N-dimethylformamide are added to a reactor at a temperature of 5°C, and stirred until the reactants are completely dissolved. Then, 1075.0g 4,4'-(hexafluoroisopropylene) diphthalic anhydride is added to the reactor in three times. After the addition is completed, the reactor is stably raised to 30°C and kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to a rotary evaporator. The temperature of the rotary evaporator is raised to 60°C, and the modified polyamic acid is obtained after distillation under reduced pressure until no liquid is produced.

[0069] Step (ii) Preparation of hybrid polyamic acid

[0070] Weigh: 800.0g of modified polyamic acid, 200.0g of the modified chain extender prepared in step 1, 30.0g of benzoic acid and 4000.0mL of N,N-dimethylformamide, add them into a reactor and stir, raise the temperature of the reactor to 60°C, keep stirring for 60min, and after post-treatment, lower the temperature of the reactor to room temperature, transfer the reaction solution to a rotary evaporator, raise the temperature of the rotary evaporator to 60°C, and distill under reduced pressure until no liquid is produced to obtain a hybrid polyamic acid.

[0071] Example 5

[0072] The present embodiment provides a method for preparing a hybrid polyamic acid for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0073] Step (i) Preparation of modified polyamic acid

[0074] Weigh: 240.0g (E)-but-2-ene-1,4-diamine and 10000.0mL N,N-dimethylformamide are added to a reactor at a temperature of 0°C, and stirred until the reactants are completely dissolved. Then, 1120.0g 4,4'-(hexafluoroisopropylene) diphthalic anhydride is added to the reactor in three times. After the addition is completed, the reactor is stably raised to 50°C and kept warm for 4 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to a rotary evaporator. The temperature of the rotary evaporator is raised to 80°C, and the modified polyamic acid is obtained after distillation under reduced pressure until no liquid is produced.

[0075] Step (ii) Preparation of hybrid polyamic acid

[0076] Weigh: 1000.0g modified polyamic acid, 300.0g modified chain extender prepared in step 2, 50.0g benzoic acid and 5000.0mL N, N-dimethylformamide, add into the reactor and stir, heat the reactor temperature to 80°C, keep warm and stir for 80min, and after post-treatment, wait for the reaction to be completed, wait for the reactor temperature to be lowered to room temperature, transfer the reaction solution to a rotary evaporator, raise the temperature of the rotary evaporator to 80°C, and distill under reduced pressure until no liquid is produced to obtain a hybrid polyamic acid.

[0077] Example 6

[0078] The present embodiment provides a method for preparing a hybrid polyamic acid for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0079] Step (i) Preparation of modified polyamic acid

[0080] Weigh: 210.0g (E)-but-2-ene-1,4-diamine and 9000.0mL N,N-dimethylformamide are added to a reactor at a temperature of 3°C, and stirred until the reactants are completely dissolved. Then, 1100.0g 4,4'-(hexafluoroisopropylene) diphthalic anhydride is added to the reactor in three times. After the addition is completed, the reactor is stably raised to 40°C and kept warm for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to a rotary evaporator. The temperature of the rotary evaporator is raised to 70°C, and the modified polyamic acid is obtained after distillation under reduced pressure until no liquid is produced.

[0081] Step (ii) Preparation of hybrid polyamic acid

[0082] Weigh: 900.0g modified polyamic acid, 240.0g modified chain extender prepared in step 3, 40.0g benzoic acid and 4800.0mL N, N-dimethylformamide, add into the reactor and stir, raise the temperature of the reactor to 70°C, keep warm and stir for 70min, and post-treat to obtain the reaction. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is raised to 70°C, and the hybrid polyamic acid is obtained after distillation under reduced pressure until no liquid is produced.

[0083] Example 7

[0084] This embodiment provides a method for preparing a hybrid polyimide for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0085] Step (1): preparing composite polyamic acid

[0086] Weigh: 100.0 g of ethyl titanate and 1000.0 mL of deionized water, mix and stir to obtain a modification solution;

[0087] Weigh: 800.0 g of the hybrid polyamic acid prepared in step 4 and 4000.0 mL of N,N-dimethylformamide are added to the reactor. After stirring at room temperature for 10 minutes, 1000.0 mL of the modification liquid is added dropwise to the reactor. After the addition is complete, continue stirring for 3 minutes, let stand for 20 minutes, and post-treat to obtain a composite polyamic acid.

[0088] Step (2): Preparation of hybrid polyimide

[0089] 500.0 g of hybrid polyamic acid was transferred to an electric thermostat, and after nitrogen protection was introduced, the electric thermostat was heated to 100° C. After heat preservation for 60 minutes, the electric thermostat was further heated to 200° C. After heat preservation for 1 hour, the electric thermostat was heated to 300° C. again, and after heat preservation for 1 hour, it was naturally cooled to room temperature to obtain a hybrid polyimide.

[0090] Example 8

[0091] This embodiment provides a method for preparing a hybrid polyimide for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0092] Step (1): preparing composite polyamic acid

[0093] Weigh: 200.0 g of ethyl titanate and 1000.0 mL of deionized water, mix and stir to obtain a modification solution;

[0094] Weigh: 1000.0 g of the hybrid polyamic acid prepared in step 5 and 5000.0 mL of N,N-dimethylformamide are added to the reactor. After stirring at room temperature for 15 minutes, 1000.0 mL of the modification liquid is added dropwise to the reactor. After the addition is complete, continue stirring for 5 minutes, let stand for 30 minutes, and post-treat to obtain a composite polyamic acid.

[0095] Step (2): Preparation of hybrid polyimide

[0096] 500.0 g of hybrid polyamic acid was transferred to an electric thermostat, and after nitrogen protection was introduced, the electric thermostat was heated to 100° C. After heat preservation for 80 minutes, the electric thermostat was further heated to 200° C. After heat preservation for 1 hour, the electric thermostat was heated to 300° C. again, and after heat preservation for 1 hour, it was naturally cooled to room temperature to obtain a hybrid polyimide.

[0097] Example 9

[0098] This embodiment provides a method for preparing a hybrid polyimide for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0099] Step (1): preparing composite polyamic acid

[0100] Weigh: 160.0 g of ethyl titanate and 1000.0 mL of deionized water, mix and stir to obtain a modification solution;

[0101] Weigh: 900.0 g of the hybrid polyamic acid prepared in step 6 and 4800.0 mL of N,N-dimethylformamide are added to the reactor. After stirring at room temperature for 15 minutes, 1000.0 mL of the modification liquid is added dropwise to the reactor. After the addition is complete, continue stirring for 4 minutes, let stand for 25 minutes, and post-treat to obtain a composite polyamic acid.

[0102] Step (2): Preparation of hybrid polyimide

[0103] 500.0 g of hybrid polyamic acid was transferred to an electric thermostat, and after nitrogen protection was introduced, the electric thermostat was heated to 100° C. After heat preservation for 70 minutes, the electric thermostat was further heated to 200° C. After heat preservation for 1 hour, the electric thermostat was heated to 300° C. again, and after heat preservation for 1 hour, it was naturally cooled to room temperature to obtain a hybrid polyimide.

[0104] Example 10

[0105] This embodiment provides a method for preparing composite nanoparticles for preparing corona-resistant insulating varnish for enameled wire, comprising the following steps:

[0106] Step I: Preparation of modified nanoparticles

[0107] Weigh: 600.0g of methyl orthosilicate, 200.0g of tributyl borate and 6000.0mL of deionized water are slowly added into a three-necked flask equipped with a thermometer, a stirrer and a cooling reflux device in sequence. Under stirring conditions, the three-necked flask is heated to reflux, kept warm and stirred for 4 hours, the cooling reflux device is removed and replaced with a distillation device, and then 500.0g of aluminum isopropoxide is added to the reactor. The temperature of the three-necked flask is heated to 115°C and kept warm for 10 minutes. The material is transferred to a tubular furnace and nitrogen is introduced for protection. The tubular heating furnace is increased to 500°C at a rate of 5°C / min, kept warm for 5 hours, and naturally cooled to 200°C. The nitrogen is disconnected, and water vapor is introduced at a rate of 100ccm. After keeping warm for 2 hours, it is naturally cooled to obtain modified nanoparticles.

[0108] Step II: Preparation of composite nanoparticles

[0109] Weigh: 100.0 g of perfluorooctyltrimethoxysilane, 100.0 g of 3-(methacryloyloxy)propyltrimethoxysilane and 1000.0 mL of anhydrous ethanol and mix to obtain a composite modifier;

[0110] Weigh: 600.0g modified nanoparticles, 2000.0mL toluene, 1000.0mL composite modifier and 1000.0mL deionized water and add them into the reactor, use protective sodium hydroxide solution to adjust the system pH to 8, then raise the temperature of the reactor to 30°C, keep warm and stir for 30 minutes, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with anhydrous ethanol and deionized water for 3 times, transfer the filter cake to a drying oven at 60°C, and vacuum dry it to constant weight to obtain composite nanoparticles.

[0111] Embodiment 11

[0112] This embodiment provides a method for preparing composite nanoparticles for preparing corona-resistant insulating varnish for enameled wire, comprising the following steps:

[0113] Step I: Preparation of modified nanoparticles

[0114] Weigh: 800.0g of methyl orthosilicate, 300.0g of tributyl borate and 8000.0mL of deionized water are slowly added into a three-necked flask equipped with a thermometer, a stirrer and a cooling reflux device in sequence. Under stirring conditions, the three-necked flask is heated to reflux, kept warm and stirred for 5 hours, the cooling reflux device is removed and replaced with a distillation device, and then 600.0g of aluminum isopropoxide is added to the reactor. The temperature of the three-necked flask is heated to 120°C and kept warm for 20 minutes. The material is transferred to a tubular furnace and nitrogen is introduced for protection. The tubular heating furnace is increased to 500°C at a rate of 5°C / min, kept warm for 5 hours, and naturally cooled to 300°C. The nitrogen is disconnected, and water vapor is introduced at a rate of 120sccm. After keeping warm for 3 hours, it is naturally cooled to obtain modified nanoparticles.

[0115] Step II: Preparation of composite nanoparticles

[0116] Weigh: 200.0 g of perfluorooctyltrimethoxysilane, 200.0 g of 3-(methacryloyloxy)propyltrimethoxysilane and 1500.0 mL of anhydrous ethanol and mix to obtain a composite modifier;

[0117] Weigh: 800.0g modified nanoparticles, 2500.0mL toluene, 1500.0mL composite modifier and 1500.0mL deionized water and add them into the reactor, use protective sodium hydroxide solution to adjust the system pH to 10, then raise the temperature of the reactor to 40°C and stir for 40 minutes. After the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid and collect the filter cake, wash the filter cake with anhydrous ethanol and deionized water 5 times, transfer the filter cake to a drying oven at 60°C, and vacuum dry it to constant weight to obtain composite nanoparticles.

[0118] Example 12

[0119] This embodiment provides a method for preparing composite nanoparticles for preparing corona-resistant insulating varnish for enameled wire, comprising the following steps:

[0120] Step I: Preparation of modified nanoparticles

[0121] Weigh: 700.0g of methyl orthosilicate, 240.0g of tributyl borate and 7200.0mL of deionized water are slowly added into a three-necked flask equipped with a thermometer, a stirrer and a cooling and reflux device in sequence. Under stirring conditions, the three-necked flask is heated to reflux, kept warm and stirred for 5 hours, the cooling and reflux device is removed and replaced with a distillation device, and then 540.0g of aluminum isopropoxide is added to the reactor. The temperature of the three-necked flask is heated to 120°C and kept warm for 20 minutes. The material is transferred to a tubular furnace and nitrogen is introduced for protection. The tubular heating furnace is increased to 600°C at a rate of 5°C / min, kept warm for 6 hours, and naturally cooled to 250°C. The nitrogen is disconnected, and water vapor is introduced at a rate of 110sccm. After keeping warm for 3 hours, it is naturally cooled to obtain modified nanoparticles.

[0122] Step II: Preparation of composite nanoparticles

[0123] Weigh: 160.0 g of perfluorooctyltrimethoxysilane, 160.0 g of 3-(methacryloyloxy)propyltrimethoxysilane and 1200.0 mL of anhydrous ethanol and mix to obtain a composite modifier;

[0124] Weigh: 720.0g modified nanoparticles, 2100.0mL toluene, 1200.0mL composite modifier and 1200.0mL deionized water and add them into the reactor, use protective sodium hydroxide solution to adjust the system pH to 9, then raise the reactor temperature to 36°C and keep stirring for 36 minutes. After the reaction is completed, lower the reactor temperature to room temperature, filter the reaction liquid and collect the filter cake, wash the filter cake with anhydrous ethanol and deionized water 4 times, transfer the filter cake to a drying oven at 60°C, and vacuum dry it to constant weight to obtain composite nanoparticles.

[0125] Embodiment 13

[0126] This embodiment provides a method for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0127] Weigh: 180.0 g of butyl acetate, 80.0 g of toluene and 40.0 g of isopropanol and mix to obtain a composite solvent;

[0128] Weigh: 700.0g of the hybrid polyimide prepared in Example 7, 100.0g of the composite nanoparticles prepared in Example 10 and 300.0g of the composite solvent are added to the reactor and stirred. After the temperature of the reactor is raised to 60°C, 20.0g of azobisisobutyronitrile is added. After stirring for 40 minutes, 20.0g of 2-hydroxy-4-octyloxybenzophenone, 30.0g of sodium carboxymethyl cellulose, 10.0g of dimethyl silicone oil and 50.0g of diaminodiphenyl ether are added to the reactor. The mixture is stirred for 10 minutes and cooled naturally to room temperature to obtain a corona-resistant insulating paint.

[0129] Embodiment 14

[0130] This embodiment provides a method for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0131] Weigh: 200.0 g of butyl acetate, 100.0 g of toluene and 60.0 g of isopropanol are mixed to obtain a composite solvent;

[0132] Weigh: 800.0g of the hybrid polyimide prepared in Example 8, 150.0g of the composite nanoparticles prepared in Example 11 and 360.0g of the composite solvent are added to the reactor and stirred. After the temperature of the reactor is raised to 80°C, 30.0g of azobisisobutyronitrile is added. After stirring for 60min, 30.0g of 2-hydroxy-4-octyloxybenzophenone, 50.0g of sodium carboxymethyl cellulose, 20.0g of dimethyl silicone oil and 60.0g of diaminodiphenyl ether are added to the reactor. The mixture is stirred for 15min and cooled naturally to room temperature to obtain a corona-resistant insulating paint.

[0133] Embodiment 15

[0134] This embodiment provides a method for preparing a corona-resistant insulating varnish for an enameled wire, comprising the following steps:

[0135] Weigh: 180.0 g of butyl acetate, 100.0 g of toluene and 60.0 g of isopropanol and mix to obtain a composite solvent;

[0136] Weigh: 720.0g of the hybrid polyimide prepared in Example 9, 120.0g of the composite nanoparticles prepared in Example 12 and 340.0g of the composite solvent are added to the reactor and stirred. After the temperature of the reactor is raised to 80°C, 25.0g of azobisisobutyronitrile is added. After stirring for 50 minutes, 24.0g of 2-hydroxy-4-octyloxybenzophenone, 36.0g of sodium carboxymethyl cellulose, 16.0g of dimethyl silicone oil and 54.0g of diaminodiphenyl ether are added to the reactor. The mixture is stirred for 12 minutes and cooled naturally to room temperature to obtain a corona-resistant insulating paint.

[0137] Comparative Example 1

[0138] The difference between this embodiment and Comparative Example 15 is that step (1) is omitted in the preparation process of the hybrid polyimide used, and an equal amount of hybrid polyamic acid is used to replace the hybrid polyamic acid in step (2).

[0139] Comparative Example 2

[0140] The difference between this embodiment and Comparative Example 15 is that, in the preparation process of the hybrid polyimide used and the hybrid polyamic acid used, step (ii) is omitted.

[0141] Comparative Example 3

[0142] The difference between this embodiment and Comparative Example 15 is that the use of composite nanoparticles is eliminated.

[0143] Performance Test:

[0144] The anti-corona life, anti-scratch performance and solvent resistance of the corona-resistant insulating varnishes prepared in Examples 13-15 and Comparative Examples 1-3 after curing were measured with reference to the standard GB / T 24122-2009 "Corona-resistant varnishes for enameled wires";

[0145] The flame retardant properties of the cured corona-resistant insulating varnishes prepared in Examples 13-15 and Comparative Examples 1-3 were measured with reference to the standard GB 28374-2012 "Fire retardant coatings for cables";

[0146] The volume resistivity of the corona-resistant insulating paint surface after curing prepared in Examples 13-15 and Comparative Examples 1-3 was measured with reference to the standard GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials Part 2: Resistive properties (DC method) Volume resistance and volume resistivity";

[0147] With reference to the standard GB / T 16422.3-2022 "Plastics Laboratory Light Source Exposure Test Method Part 3: Fluorescent Ultraviolet Lamp", the cured paint surfaces of the corona-resistant insulating paints prepared in Examples 13-15 and Comparative Examples 1-3 were subjected to ultraviolet aging tests, and the paint scraping pressure retention rate of the paint surface was determined with reference to the standard GB / T 24122-2009. The specific data are shown in Table 1.

[0148] Table 1-Performance test data of each sample

[0149]

[0150] Data Analysis:

[0151] Comparing and analyzing the data in Table 1 above, the corona resistance performance of the corona resistant insulating paint prepared by the present invention after curing is 5h, the paint scraping pressure is 13.2N, the hardness after solvent immersion is 3H, the carbonization height is 1.1m, and the volume resistivity is 3.78×10 16 Ω·m, and the paint scraping pressure retention rate after UV aging is 98.9%, all data are better than the control ratio;

[0152] The present invention constructs a rigid and flexible polyimide main chain by introducing a polysiloxane chain extender. The flexible siloxane chain segment is combined with the rigid aromatic ring through hydrogen bonds, thereby improving the interface compatibility and mechanical toughness while maintaining the high temperature resistance of the material, and inhibiting local discharge caused by microcracks. Secondly, the nano-titanium dioxide particles and the silicon-aluminum-boron composite particles modified with fluorine groups work synergistically. Titanium dioxide disperses the electric field evenly through its high dielectric properties, and the fluorine groups capture free electrons with their strong electronegativity to form a hydrophobic barrier, blocking moisture penetration and active oxygen erosion. A three-dimensional cross-linked network is further constructed through free radical reactions, and the double bonds on the surface of the silicon-aluminum-boron particles form dynamic bonds with the polyimide main chain. Energy dissipation is achieved through molecular chain slippage under electric field stress, avoiding breakdown caused by charge concentration, thereby significantly improving the anti-corona, insulation and solvent resistance of the insulating paint.

[0153] The siloxane chain extender prepared by the present invention forms a rigid and flexible structure through the flexible chain segment and the rigid main chain of the polyimide, which not only maintains the high strength characteristics of the material, but also disperses the mechanical stress through the slippage of the molecular chain, and combines the hard support and uniform dispersion of the nano titanium dioxide particles to form physical crosslinking points to resist friction and wear, inhibit the expansion of surface cracks, and in the combustion process, the fluorine-containing free radicals generated by the high-temperature decomposition of the fluorine group interrupt the combustion chain reaction, and a dense oxide layer is formed on the surface of the silicon aluminum boron particles when heated to isolate oxygen and heat transfer, and the boron element catalyzes the rapid generation of a carbonized layer, further blocking the spread of flames; the fluorine group-modified nanoparticles strongly bind to the polymer interface to inhibit crack expansion, and the rigid support of the crosslinked network complements the flexible buffer of the siloxane chain, thereby significantly improving the flame retardancy and wear resistance of the insulating paint;

[0154] A large number of fluorine groups in the insulating varnish prepared by the present invention absorb ultraviolet light energy through strong electronegativity and convert it into heat energy for release. Its chemical inertness forms a dense barrier to block the direct damage of ultraviolet rays to the polymer main chain. At the same time, the hydrophobic property inhibits the synergistic photooxidation reaction of water vapor. The nano titanium dioxide particles reflect and scatter ultraviolet rays by virtue of their high refractive index characteristics, reducing their penetration depth. The evenly dispersed particles are chemically bonded to the polymer chains to synergistically inhibit the breakage of the molecular chains. The perfluorinated groups modified on the surface of the silicon-aluminum-boron composite nanoparticles are cross-linked with the polyimide chain segments through double bonds through free radical reactions to form a spatial cross-linked network, fix the position of the particles to enhance the density of the coating, reduce the extension of ultraviolet-induced microcracks, and the high thermal conductivity assists the diffusion of heat energy to avoid local heating and accelerated aging, thereby significantly improving the anti-ultraviolet performance of the insulating varnish.

[0155] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A corona-resistant insulating varnish for enameled wire, characterized in that: The method comprises the following raw materials in parts by weight: 70-80 parts of hybrid polyimide, 10-15 parts of composite nanoparticles, 30-36 parts of composite solvent and 6-8 parts of auxiliary additives; The preparation method of the hybrid polyimide comprises the following steps: A1, adding hybrid polyamic acid and N, N-dimethylformamide into a reactor, stirring at room temperature for 10-15 minutes, adding modification liquid to the reactor, stirring for 3-5 minutes after the addition is complete, standing for 20-30 minutes, and post-treating to obtain composite polyamic acid; A2. Thermal imidization of the composite polyamic acid to obtain a hybrid polyimide.

2. The corona-resistant insulating varnish for enameled wire according to claim 1, characterized in that: In step A1, the amount ratio of hybrid polyamic acid, N,N-dimethylformamide and modifying liquid is 8-10g:40-50mL:10mL, wherein the modifying liquid is obtained by mixing and stirring ethyl titanate and deionized water at an amount ratio of 1-2g:10mL; in step A2, the preparation method of hybrid polyimide is: transferring the hybrid polyamic acid to an electric thermostat, introducing nitrogen protection, heating the electric thermostat to 100°C, and keeping the temperature for 60-80min. The electric thermostat continues to heat up to 200°C, and after keeping the temperature for 1h, the electric thermostat is heated to 300°C again, and after keeping the temperature for 1h, it is naturally cooled to room temperature to obtain a composite polyimide.

3. The corona-resistant insulating varnish for enameled wire according to claim 1, characterized in that: The preparation method of the hybrid polyamic acid comprises the following steps: B1. Add (E)-but-2-ene-1,4-diamine and N,N-dimethylformamide to a reactor at a temperature of 0-5°C, keep warm and stir until the reactants are completely dissolved, add 4,4'-(hexafluoroisopropylene) diphthalic anhydride to the reactor in three portions, and after the addition is completed, stably raise the temperature of the reactor to 30-50°C, keep warm and react for 2-4 hours, and post-treat to obtain modified polyamic acid; B2. Add modified polyamic acid, modified chain extender, benzoic acid and N,N-dimethylformamide into a reactor and stir. Heat the reactor to 60-80°C, keep warm and stir for 60-80 minutes, and perform post-treatment to obtain hybrid polyamic acid.

4. The corona-resistant insulating varnish for enameled wire according to claim 3, characterized in that: The preparation method of the modified chain extender comprises the following steps: C1. Add 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3-dimethyl-1,1,3,3-tetravinyldisiloxane and diethyl ether into a reactor and stir. Add 98wt% concentrated sulfuric acid during stirring. After stirring at room temperature for 8-10h, add sodium bicarbonate powder into the reactor to adjust the pH value of the system to 8-9. Post-treat to obtain modified silicone oil. C2. Add modified silicone oil, benzoic acid, aluminum chloride and dimethyl sulfoxide into a reactor and stir. The temperature of the reactor is lowered to 0-5°C. Saturated hydrogen peroxide solution is added dropwise to the reactor under stirring and heat preservation. The addition operation is maintained for 3-4 hours. After the addition is completed, the reactor is stirred and heat preservation for 1 hour. The modified chain extender is obtained by post-treatment.

5. The corona-resistant insulating varnish for enameled wire according to claim 4, characterized in that: In step C1, the amount ratio of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 1,3-dimethyl-1,1,3,3-tetravinyldisiloxane, ether and 98wt% concentrated sulfuric acid is 7-9g:2-3g:50-80mL:10-12mL; in step C2, the amount ratio of modified silicone oil, benzoic acid, aluminum chloride, dimethyl sulfoxide and saturated hydrogen peroxide solution is 12-16g:3-5g:0.5-0.8g:60-80mL:10-12mL.

6. The corona-resistant insulating varnish for enameled wire according to claim 1, characterized in that: The preparation method of the composite nanoparticles comprises the following steps: D1. Slowly add methyl orthosilicate, tributyl borate and deionized water to a three-necked flask equipped with a thermometer, a stirrer and a cooling reflux device in sequence. Heat the three-necked flask to reflux under stirring, keep it warm and stir for 4-5 hours, remove the cooling reflux device and replace it with a distillation device, then add aluminum isopropoxide to the reactor, heat the three-necked flask to 115-120° C., keep it warm for 10-20 minutes, and post-treat to obtain modified nanoparticles; D2. Add modified nanoparticles, toluene, composite modifier and deionized water into the reactor, use protective sodium hydroxide solution to adjust the system pH to 8-10, then increase the temperature of the reactor to 30-40°C, keep warm and stir for 30-40 minutes, and post-treat to obtain composite nanoparticles.

7. A method for preparing the corona-resistant insulating varnish for enameled wire according to any one of claims 1 to 6, characterized in that: The hybrid polyimide, composite nanoparticles and composite solvent are added to a reactor and stirred. After the temperature of the reactor is raised to 60-80°C, an initiator is added. After stirring for 40-60 minutes, an ultraviolet absorber, a thickener, a leveling agent and a hardener are added to the reactor. After stirring for 10-15 minutes, the reactor is naturally cooled to room temperature to obtain a corona-resistant insulating paint.

Citation Information

Patent Citations

  • A corona-resistant enameled wire varnish and its preparation method

    CN105219233B

  • Polyimide, resin composition, resin film, laminate, cover film, copper foil with resin, metal-clad laminate, and circuit board

    CN115122735A

  • Preparation method of nano fluorine modified silicon dioxide and polyimide composite film

    CN117700735A

  • Corona-resistant enameled wire and preparation method thereof

    CN118629707A

Cited By

  • Preparation method of aluminum-based enameled wire for automobile

    CN120126865A

  • A method for preparing aluminum-based enameled wire for automobiles

    CN120126865B

  • Ultraviolet-aging-resistant high-toughness wind power cable and preparation method thereof

    CN120319530A

  • A high-toughness wind power cable resistant to ultraviolet aging and its preparation method

    CN120319530B